Solving 28 nm I/O circuit reliability issue due to IC design weakness. (September 2018) - Low, Yi Chao; Tan, P.K.; Tan, S.L.; Zhao, Y.Z.; Lam, J.
Abstract: Integrated circuit (IC) reliability failure at field presents significant cost to both manufacturer and consumer. This paper targets reliability issue due to IC design weakness, presenting a case of 28 nm Input/Output (I/O) circuit reliability failure, and shows a complete work flow, starting from root cause identification using Final Test (FT) and failure analysis (FA), and ending with design retrofit to solve the issue. The work flow solves a 28 nm I/O reliability issue successfully (a narrow metal leads to EOS at field, and design retrofit is done to enlarge metal's current carrying capability). The work flow is applicable to solve general design related reliability problems. Highlights: Complete methodology to solve IC reliability issue due to IC design weak point Starts with weak point identification using chip testing and failure analysis, and ends with IC design retrofit 28nm chip case study: Inadequate estimation of electrical load requirement during IC design stage leads to EOS at field